Developing a Collaborative Research Hub in University Libraries: A Strategy to Enhance Faculty Research Productivity - Haryanto, Haryanto; Dewi, Dinar Puspita; Haryanti, Rina Herlina (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
University libraries are increasingly expected to transform into research centers that support academic productivity, particularly for faculty members. This study aims to develop a Collaborative Research Hub (CRH) model at the Sebelas Maret University Library (UPT Perpustakaan UNS) as a strategy to enhance research services through collaboration and technology. Using a qualitative approach and guided by the principles of user-centered design, the research was conducted in three stages: user needs analysis, prototype development and testing, and model evaluation. The findings show that 86.7% of respondents need collaborative workspaces, 80% require access to international journals, and 76.7% seek technical assistance in reference management. Prototype testing indicated that 83% of faculty participants found the CRH model effective in supporting their research activities. In addition, the role of librarians as research facilitators and the integration of library information systems received positive feedback. However, the evaluation also revealed the need to enhance system interoperability, offer more flexible and responsive services, and strengthen librarian competencies in supporting scholarly writing and publication. The uneven distribution of skills highlights the importance of continuous professional development to ensure that librarians can serve as strategic research partners. This study concludes that the CRH model improves research efficiency and fosters interdisciplinary academic collaboration. The model offers a replicable framework for strengthening library-based research services across higher education institutions.